2014
DOI: 10.1186/1678-9199-20-48
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Leiurus abdullahbayrami (Scorpiones: Buthidae) venom: peptide profile, cytotoxicity and antimicrobial activity

Abstract: BackgroundScorpion venoms are rich bioactive peptide libraries that offer promising molecules that may lead to the discovery and development of new drugs. Leiurus abdullahbayrami produces one of the most potent venoms among Turkish scorpions that provokes severe symptoms in envenomated victims.MethodsIn the present study, the peptide profile of the venom was investigated by electrophoretic methods, size-exclusion and reversed-phase chromatography and mass spectroscopy. Cytotoxic and antimicrobial effects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 24 publications
2
13
0
7
Order By: Relevance
“…Top-down data sets showed that the venom of B.occitanus is very complex, counting around 200 molecular weights ranging from 1868 to 16 720 Da. A similar number of components have been revealed by previous studies [32,33,34], others showed fewer components, as well as Leiurus abdullahbayrami (45 masses) and Opisthacanthus elatus (106 masses) [35,36], whereas some others scorpion venoms were more complex, such as the Pandinus cavimanus (390 masses) and…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Top-down data sets showed that the venom of B.occitanus is very complex, counting around 200 molecular weights ranging from 1868 to 16 720 Da. A similar number of components have been revealed by previous studies [32,33,34], others showed fewer components, as well as Leiurus abdullahbayrami (45 masses) and Opisthacanthus elatus (106 masses) [35,36], whereas some others scorpion venoms were more complex, such as the Pandinus cavimanus (390 masses) and…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, the repartition of molecular weights showed that less than 1% were components with molecular masses <2000 Da, 14% those from 2000 to 5000 Da, 74% those between 5000 to 8000 Da, and 10% were those over than 8000 Da, while the repartition of molecular weights from the French B.occitanus scorpion venom showed an abundance of molecules ranging from 2000 to 3000 Da and those less than 2000 Da [39]. revealed by previous studies [32,33,34], others showed fewer components, as well as Leiurus abdullahbayrami (45 masses) and Opisthacanthus elatus (106 masses) [35,36] whereas some others scorpion venoms were more complex, such as the Pandinus cavimanus (390 masses) and…”
Section: Discussionmentioning
confidence: 82%
“…The venom increased the viability of HeLa cells at lower doses (1.25 and 2.5 μg/ml). This effect can be observed for snake venoms and also scorpion venoms because of proteins, peptides and other organic compounds that may promote cell proliferation at lower concentrations (Mesquita-Ferrari et al 2009;Erdeş et al 2014;Yalcin et al 2014). According to the results, HeLa (IC 50 = 12.80 μg/ml) is the most resistant cell line against all venom doses, while Vero and U-87 MG cell lines seem to be the most sensitive of the tested cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the svAMPs from M. eupeus showed more potent activity on Gram-positive bacteria than on Gram-negative bacteria. This is obviously different from venoms from scorpions Leiurus abdullahbayrami, Parabuthus schlechteri , and Opistophthalmus carinatus , which are more active on Gram-negative bacteria (Moerman et al, 2002 ; Erdeş et al, 2014 ). This difference could be a reflection of ecological adaptation of scorpions to different micobial species in their habitats, strengthening the roles of these peptides in scorpion immunity.…”
Section: Discussionmentioning
confidence: 93%